Familial inheritance of TMD: a case report - Maria Genello (University Library System, University of Pittsburgh, 2017)
The TMJ is a joint that can perform both hinge and sliding motions and whose proper functioning depends on the actions of the joint and joint capsule, the muscles of mastication, and the condition and action of the mandibular condyle. If any of these components deviate from their normal structure or function, then TMD can result. There have been many reported contributing factors to TMD development, many of which include environmental influences such as bruxism, trauma, and other oral habits. However, a genetic component can also play a role. This paper reports a case of TMD occurring within three consecutive generations of a family and explores the possibility of this disorder exhibiting familial inheritance. Members of the family affected all displayed manifestations of joint laxity in other areas of the body, migraines, pain, and had smaller craniofacial dimensions with a narrower mandible. These factors were found to have a genetic influence and these genes can also be tied to TMD, thus supporting the argument that the cases of TMD seen in this family are in fact due to inheritance. If TMD can be shown to have a genetic component and be inherited, then dental practitioners would be able to identify high risk patients and help to modify environmental factors early on in order to help prevent the onset of TMD in those individuals.